Solid Adsorbents for Low-Temperature CO2 Capture with Low-Energy Penalties Leading to More Effective Integrated Solutions for Power Generation and Industrial Processes - Sun, Nannan; Tang, Zhiyong; Wei, Wei; Snape, Colin Edward; Sun, Yuhan (Frontiers in Energy Research, 2015)
CO2 capture represents the key technology for CO2 reduction within the framework of CO2 capture, utilization, and storage (CCUS). In fact, the implementation of CO2 capture extends far beyond CCUS since it will link the CO2 emission and recycling sectors, and when renewables are used to provide necessary energy input, CO2 capture would enable a profitable zero- or even negative-emitting and integrated energy-chemical solution. To this end, highly efficient CO2 capture technologies are needed, and adsorption using solid adsorbents has the potential to be one of the ideal options. Currently, the greatest challenge in this area is the development of adsorbents with high performance that balances a range of optimization-needed factors, those including costs, efficiency, and engineering feasibility. In this review, recent advances on the development of carbon-based and immobilized organic amines-based CO2 adsorbents are summarized, the selection of these particular categories of materials is because they are among the most developed low temperature (<100 oC) CO2 adsorbents up to date, which showed important potential for practical deployment at pilot-scale in the near future. Preparation protocols, adsorption behaviors as well as pros and cons of each type of the adsorbents are presented, it was concluded that encouraging results have been achieved already, however, the development of more effective adsorbents for CO2 capture remains challenging and further innovations in the design and synthesis of adsorbents are needed.